2015
DOI: 10.1038/srep15700
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic recording of myosin head power stroke in hydrated myosin filaments

Abstract: Muscle contraction results from cyclic attachment and detachment between myosin heads and actin filaments, coupled with ATP hydrolysis. Despite extensive studies, however, the amplitude of myosin head power stroke still remains to be a mystery. Using the gas environmental chamber, we have succeeded in recording the power stroke of position-marked myosin heads in hydrated mixture of actin and myosin filaments in a nearly isometric condition, in which myosin heads do not produce gross myofilament sliding, but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Since the junctional peptide is located in between the two main actin binding sites of myosin heads [1], it seems clear that the antibody attached to the junctional peptide completely covers the two actin binding sites, so that formation of rigor linkages between actin and myosin head is no longer possible. If this explanation is correct, the result of our EC experiments, that individual myosin heads can perform ATP-induced power stroke [23], [24] may be taken to imply that, in the actin-myosin interaction cycle taking place in muscle, myosin heads do not pass through rigor configurations, which is generally believed to exist in the actomyosin ATPase reaction steps [26]. This idea is supported by our recent experiments that this antibody has no effect on both ATP-dependent vitro actin-myosin sliding and Ca 2+ -activated muscle fiber contraction [27].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Since the junctional peptide is located in between the two main actin binding sites of myosin heads [1], it seems clear that the antibody attached to the junctional peptide completely covers the two actin binding sites, so that formation of rigor linkages between actin and myosin head is no longer possible. If this explanation is correct, the result of our EC experiments, that individual myosin heads can perform ATP-induced power stroke [23], [24] may be taken to imply that, in the actin-myosin interaction cycle taking place in muscle, myosin heads do not pass through rigor configurations, which is generally believed to exist in the actomyosin ATPase reaction steps [26]. This idea is supported by our recent experiments that this antibody has no effect on both ATP-dependent vitro actin-myosin sliding and Ca 2+ -activated muscle fiber contraction [27].…”
Section: Discussionmentioning
confidence: 88%
“…In our EC experiments [23], individual myosin heads are position-marked by a monoclonal antibody directed to the junctional peptide between 50- and 20-kDa segments of myosin heavy chain [25]. Since the junctional peptide is located in between the two main actin binding sites of myosin heads [1], it seems clear that the antibody attached to the junctional peptide completely covers the two actin binding sites, so that formation of rigor linkages between actin and myosin head is no longer possible.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To position-mark individual myosin heads, colloidal gold particles (diameter, 15 nm; coated with protein A) were attached to myosin heads via site-directed monoclonal antibody to distal region of myosin head. Further details of the methods have been described elsewhere [8,9]. Figure 8 shows electron micrograph of myosinmanner.…”
Section: Attachment-detachment Cycle Between Myosin Heads and Actin Fmentioning
confidence: 99%
“…Nevertheless, Harrington intended to demonstrate the important role of S-2 hinge region in muscle contraction, and prepared a polyclonal antibody to S-2 hinge region (anti-S-2 antibody), and showed that the antibody reduced Ca 2+ - Figure 6: Schematic diagram illustrating the helix to (random) coil transition cycle occurring in myosin-S-2 hinge region proposed by Harrington [9]. Helical and random coil structures of the S-2 hinge region are expressed as straight and zig-zag shapes, respectively [7].…”
Section: Proposal Of the Helix-coil Transition Theory By Harringtonmentioning
confidence: 99%